# What is the axis of symmetry for -x^2-2x+6

QUESTION POSTED AT 28/05/2020 - 11:58 PM

QUESTION POSTED AT 28/05/2020 - 11:58 PM

By using completing the Square method ,

-x^2-2x+6

= - ( x^2+2x-6) -> factorise -1

= - ( ( x+1 )^2 - (1)^2 -6 ) -> complete the square

= - ( x+1 )^2 +7

- ( x+1 )^2 =0 -> equip it to 0

-x-1 =0

X = -1

axis of symmetry : x = -1

-x^2-2x+6

= - ( x^2+2x-6) -> factorise -1

= - ( ( x+1 )^2 - (1)^2 -6 ) -> complete the square

= - ( x+1 )^2 +7

- ( x+1 )^2 =0 -> equip it to 0

-x-1 =0

X = -1

axis of symmetry : x = -1

QUESTION POSTED AT 02/06/2020 - 01:18 AM

QUESTION POSTED AT 01/06/2020 - 04:45 PM

QUESTION POSTED AT 01/06/2020 - 04:38 PM

QUESTION POSTED AT 01/06/2020 - 04:32 PM

QUESTION POSTED AT 01/06/2020 - 04:19 PM

QUESTION POSTED AT 01/06/2020 - 03:57 PM

QUESTION POSTED AT 01/06/2020 - 03:29 PM

QUESTION POSTED AT 01/06/2020 - 03:26 PM

QUESTION POSTED AT 01/06/2020 - 03:13 PM

QUESTION POSTED AT 01/06/2020 - 02:50 PM

QUESTION POSTED AT 01/06/2020 - 02:45 PM

QUESTION POSTED AT 01/06/2020 - 02:38 PM

QUESTION POSTED AT 01/06/2020 - 02:22 PM

QUESTION POSTED AT 01/06/2020 - 12:11 PM

QUESTION POSTED AT 01/06/2020 - 11:54 AM

QUESTION POSTED AT 29/05/2020 - 05:29 PM

QUESTION POSTED AT 29/05/2020 - 04:33 PM

QUESTION POSTED AT 29/05/2020 - 04:18 PM

QUESTION POSTED AT 29/05/2020 - 02:56 PM

QUESTION POSTED AT 29/05/2020 - 02:51 PM

QUESTION POSTED AT 29/05/2020 - 02:35 PM

QUESTION POSTED AT 29/05/2020 - 01:55 PM

QUESTION POSTED AT 29/05/2020 - 12:40 PM

QUESTION POSTED AT 29/05/2020 - 12:22 PM

QUESTION POSTED AT 29/05/2020 - 11:01 AM

QUESTION POSTED AT 29/05/2020 - 10:48 AM